2008
DOI: 10.1108/08876040810862895
|View full text |Cite
|
Sign up to set email alerts
|

Toward a measure of service convenience: multiple‐item scale development and empirical test

Abstract: PurposeThe purpose of this paper is to report on the development and nomological testing of a 17‐item scale measuring the five dimensions of service convenience (decision, access, transaction, benefit, and post‐benefit) as proposed by Berry, Seiders, and Grewal.Design/methodology/approachA cross‐sectional survey methodology was used to collect the data.FindingsReliability and validity assessments provided evidence of the scale's psychometric validity. Service convenience was found to be a significant predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
1
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(274 citation statements)
references
References 31 publications
13
235
1
25
Order By: Relevance
“…Kenyamanan layanan merupakan persepsi pelanggan mengenai waktu dan usaha yang dikeluarkan oleh pelanggan terkait dengan pembelian atau penggunaan produk atau jasa (Berry et al, 2002), sehingga untuk meningkatkan kenyamanan layanan pelanggan dapat dilakukan dengan usaha untuk menurunkan waktu yang dibutuhkan untuk melayanani pelanggan dan mengurangi usaha yang harus dikeluarkan pelanggan (Colwell et al, 2008). Penelitian ini menggunakan konsep kenyamanan layanan menurut Berry et al, (2002), yang membagi kenyamanan layanan menjadi lima dimensi, yaitu kenyamanan dalam mengambil keputusan, kenyamanan akses, kenyamanan transaksi, kenyamanan memperoleh manfaat, kenyamanan pasca layanan.…”
Section: Bunclassified
See 1 more Smart Citation
“…Kenyamanan layanan merupakan persepsi pelanggan mengenai waktu dan usaha yang dikeluarkan oleh pelanggan terkait dengan pembelian atau penggunaan produk atau jasa (Berry et al, 2002), sehingga untuk meningkatkan kenyamanan layanan pelanggan dapat dilakukan dengan usaha untuk menurunkan waktu yang dibutuhkan untuk melayanani pelanggan dan mengurangi usaha yang harus dikeluarkan pelanggan (Colwell et al, 2008). Penelitian ini menggunakan konsep kenyamanan layanan menurut Berry et al, (2002), yang membagi kenyamanan layanan menjadi lima dimensi, yaitu kenyamanan dalam mengambil keputusan, kenyamanan akses, kenyamanan transaksi, kenyamanan memperoleh manfaat, kenyamanan pasca layanan.…”
Section: Bunclassified
“…Berdasarkan penelitian sebelumnya, maka hipotesis kedua penelitian ini adalah. H2 : Persepsi kewajaran harga berpengaruh positif dan signifikan terhadap kepuasan pelanggan Persaingan usaha semakin ketat dan dinamis, mendorong pelaku usaha untuk meningkatkan kepuasan pelanggan, salah satunya adalah dengan meningkatkan kenyamanan pelanggan (Colwell et al, 2008), karena pelanggan menuntut peningkatan kenyamanan (Dabholkar et al, 2003). Penelitian tersebut menunjukan bahwa persepsi pelanggan terhadap kenyamanan berpengaruh positif dan signifikan terhadap kepuasan pelanggan, sehingga semakin tinggi tingkat kenyamanan yang dirasakan pelanggan, maka kepuasan pelanggan meningkat.…”
Section: Hipotesisunclassified
“…Many studies have shown that shopping convenience is one of the main factors boosting the popularity of online shopping [8,9]. According to Farquhar and Rowley [10], convenience is considered as a customer resource than an attribute of service.…”
Section: Introductionmentioning
confidence: 99%
“…Berry et al (2002) provide a model of service convenience and state that service convenience is consumers' time and effort perceptions of (1) decision convenience, (2) access convenience, (3) transaction convenience, (4) benefit convenience, and (5) post benefit convenience. Using Berry et al (2002) framework, Colwell, et al (2008) find that service convenience is positively associated with customer satisfaction. Similarly, Kim et al (2006) find that convenience of an online market place positively influences customer satisfaction.…”
Section: Convenience Of Service (Cos)mentioning
confidence: 99%
“…Furthermore, future research can be conducted to investigate the influence of interaction of basic human values (Schwartz et al, 2012) and facets of perceived risk (Featherman & Pavlou, 2003) on the relationships identified in our research. Lastly, future research can also be conducted by utilizing the service convenience scale (Colwell et al, 2008) to…”
Section: Conclusion and Future Researchmentioning
confidence: 99%